[Mount St. Benedict, Trinidad, B.W.I.] - (:unkn) unknown (My University, 2010)
Photograph of Mount St. Benedict in Trinidad and Tobago.
Colour: White, Grey and Cream Hues; Style: Landscape; Other: Bordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Mountains--Trinidad and Tobago; Catholic Church--Trinidad and Tobago; Christianity--Trinidad and Tobago; Catholics--Trinidad and Tobago; Monasteries--Trinidad and Tobago; Catholic church buildings--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Mt. St. Benedict